2019
DOI: 10.3390/molecules24183378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PLA/PBAT Antibacterial Film on Storage Quality of Passion Fruit during the Shelf-Life

Abstract: In this experiment, we studied the effect of poly(lactic acid)/poly(butylene adipate-co-terephthalate) (PLA/PBAT) blend films on the efficiency of passion fruit preservation at 20 °C. The weight loss, shrinkage index, firmness, and total sugar of passion fruit packaged with PLA/PBAT films had no significant differences compared with PE films during 21 days (p > 0.05). PLA/PBAT films can more effectively reduce the rising of ethanol content and delay the total acid, ascorbic acid, and sensory evaluation. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
1
10
0
3
Order By: Relevance
“…Vitamin C and titratable acids degradation was mainly caused by the exposure of respiration and ripeness. Similar results were also observed by Rong et al, (2019) concluded that the weight loss, shrinkage index, firmness, and total sugar of passion fruit packaged with poly(lactic acid)/poly (butylene adipate -co-terephthalate) films had no significant differences compared with PE films during 21 days (p > 0.05) preservation at 20°C. Peninah et al, (2014) indicated that active bags can prolong the shelf life by maintaining quality attributes and external appearance of purple passion fruits and hence extend their marketing period.…”
Section: Results and Dicussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Vitamin C and titratable acids degradation was mainly caused by the exposure of respiration and ripeness. Similar results were also observed by Rong et al, (2019) concluded that the weight loss, shrinkage index, firmness, and total sugar of passion fruit packaged with poly(lactic acid)/poly (butylene adipate -co-terephthalate) films had no significant differences compared with PE films during 21 days (p > 0.05) preservation at 20°C. Peninah et al, (2014) indicated that active bags can prolong the shelf life by maintaining quality attributes and external appearance of purple passion fruits and hence extend their marketing period.…”
Section: Results and Dicussionsupporting
confidence: 85%
“…The increase of total sugar content was mainly due to maturation and changing titratable acids. Rong Zhang, 2019 shown that the sharpest increase of total sugar was changed PLA/PABT-and PE-packaged samples (8.25% and 8.55%, respectively) after 15 days. The content of vitamin C (Fig.…”
Section: Results and Dicussionmentioning
confidence: 96%
“…4,5 As one of the most produced biodegradable plastics, poly(butylene adipate-co-terephthalate) (PBAT) exhibits high elongation at break, excellent flexibility and good processability comparable to polyethylene, 6,7 thus showing great application prospect in agriculture and packaging. [8][9][10] However, the disadvantages of high cost, [11][12][13][14] short shelf life, 8,15,16 poor weather and water resistance [17][18][19] and poor gas barrier properties 20,21 still limit its wide application.…”
Section: Introductionmentioning
confidence: 99%
“…According to a previous article, the incorporation of a high-toughness compatible biopolymer such as polybutylene adipate-co-terephthalate (PBAT) into the PLA matrix can effectively improve the material’s toughness and flexibility [ 14 ]. This high-toughness polymer has been commonly used for packaging or agricultural purposes [ 15 , 16 ]. Only a few studies have mentioned it as a biomaterial for tissue regenerative applications.…”
Section: Introductionmentioning
confidence: 99%